Association of nasopharyngeal viruses and pathogenic bacteria in children and their parents with and without HIV - Tila Khan; Ranjan Saurav Das; Amrita Chaudhary; Jyotirmoy Chatterjee; Sangeeta Das Bhattacharya (Pneumonia, 2021)
Abstract Background Bacteria and respiratory viruses co-occur in the nasopharynx, and their interactions may impact pathogenesis of invasive disease. Associations of viruses and bacteria in the nasopharynx may be affected by HIV. Methods We conducted a nested case-control study from a larger cohort study of banked nasopharyngeal swabs from families with and without HIV in West Bengal India, to look at the association of viruses and bacteria in the nasopharynx of parents and children when they are asymptomatic. Quantitative polymerase chain reaction for 4 bacteria and 21 respiratory viruses was run on 92 random nasopharyngeal swabs from children--49 from children living with HIV (CLH) and 43 from HIV uninfected children (HUC)-- and 77 swabs from their parents (44 parents of CLH and 33 parents of HUC). Results Bacteria was found in 67% of children, viruses in 45%, and both in 27% of child samples. Staphylococcus aureus (53%) was the most common bacteria, followed by Streptococcus pneumoniae (pneumococcus) (37%) in children and parents (53, 20%). Regardless of HIV status, viruses were detected in higher numbers (44%) in children than their parents (30%) (p = 0.049), particularly rhinovirus (p = 0.02). Human rhinovirus was the most frequently found virus in both CLH and HUC. Children with adenovirus were at six times increased risk of also having pneumococcus (Odds ratio OR 6, 95% CI 1.12–31.9) regardless of HIV status. In addition, the presence of rhinovirus in children was associated with increased pneumococcal density (Regression coeff 4.5, 1.14–7.9). In CLH the presence of rhinovirus increased the risk of pneumococcal colonization by nearly sixteen times (OR 15.6, 1.66–146.4), and, pneumococcus and S. aureus dual colonization by nearly nine times (OR 8.7). Conclusions Children more frequently carried viruses regardless of HIV status. In CLH the presence of rhinovirus, the most frequently detected virus, significantly increased co-colonization with pneumococcus and S. aureus.